2003
DOI: 10.1111/j.1365-2621.2003.tb07010.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural Changes of Natural Cheddar Cheese During the Maturation Process

Abstract: Texture parameters of commercial natural cheddar cheese were tracked over the maturation period (11-mo) but not to evaluate optimal or desirable characteristics. Large strain analysis was performed using the TA-XT2 Texture Analyzer. Monitoring of chemical composition and degree of proteolysis and the solid proportions of milk fat were undertaken with differential scanning calorimeter. Fracture properties, force, and degree of compression confirmed a reduction in cheese firmness and an increase in cheese crumbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
(10 reference statements)
5
14
0
Order By: Relevance
“…Loading 3 is characterised by a trough at 930 nm and a peak at 962 nm that may originate in oil and water, respectively. It is interesting to note that while alterations in protein structure have been identified as a major feature in cheese maturation (Fox et al, 1993;Pollard et al, 2003), no significant features which may be related to protein (normally apparent between 1000 and 1100 nm; Osborne et al, 1993) occur until loadings 4 and 5.…”
Section: Prediction Of Age By Nir Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…Loading 3 is characterised by a trough at 930 nm and a peak at 962 nm that may originate in oil and water, respectively. It is interesting to note that while alterations in protein structure have been identified as a major feature in cheese maturation (Fox et al, 1993;Pollard et al, 2003), no significant features which may be related to protein (normally apparent between 1000 and 1100 nm; Osborne et al, 1993) occur until loadings 4 and 5.…”
Section: Prediction Of Age By Nir Spectroscopymentioning
confidence: 97%
“…In the particular case of hard cheeses such as Cheddar, this requires the monitoring of product through a storage and maturation phase as well as the observance of good manufacturing practice during primary production. During this maturation or ripening phase, cheese undergoes a complex series of chemical, bacterial and enzymatic reactions which are responsible for breakdown of the protein matrix and ultimately the development of the texture and sensory characteristics that are typical of mature cheese (Fox, Law, McSweeney, & Wallace, 1993;Pollard, Sherkat, Seuret, & Halmos, 2003). Determination of the degree of ripening or maturation and various sensory characteristics is an important part of cheese quality evaluation and currently involves the use of trained sensory panellists or individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Models with significant correlations between biochemical analysis and sensory descriptors provide information to better understand how proteolysis during cheese ripening is related to quality characteristics of matured cheese. Sensory descriptors such as bitterness (Frister, Michaelis, Schwerdtfeger, Folkenberg, & Sørensen, 2000) and firmness (Pollard, Sherkat, Seuret, & Halmos, 2003) are correlation based on previous research, are likely to be connected with the proteolytic development in cheese during ripening and were also in this study found to have significant values of R. Besides developing mathematical/statistical models that could predict sensory quality in cheeses based on biochemical analysis of proteolysis, regression models from PLS1 provide also a way to evaluate the importance of different biochemical properties on development of sensory descriptors.…”
Section: Article In Pressmentioning
confidence: 99%
“…Decreases in firmness, i.e., peak force at fracture point, fracture stress and fracture strain have been reported to occur during maturation of Cheddar cheese (Creamer and Olson 1982; Prentice et al. 1993; Pollard et al. 2003).…”
Section: Introductionmentioning
confidence: 99%